Assessment of Plasmodium falciparum drug resistance associated molecular markers in Mandla, Madhya Pradesh, India - Akansha Singh; Mrigendra P. Singh; Nazia Anwar Ali; Rajan Poriya; Harsh Rajvanshi; Sekh Nisar; Sneha Bhandari; Ram S. Sahu; Himanshu Jayswar; Ashok K. Mishra; Aparup Das; Harpreet Kaur; et al. (Malaria Journal, 2023)
Abstract Background Resistance against artemisinin-based combination therapy is one of the challenges to malaria control and elimination globally. Mutations in different genes (Pfdhfr, Pfdhps, Pfk-13 and Pfmdr1) confer resistance to artesunate and sulfadoxine–pyrimethamine (AS + SP) were analysed from Mandla district, Madhya Pradesh, to assess the effectiveness of the current treatment regimen against uncomplicated Plasmodium falciparum. Methods Dried blood spots were collected during the active fever survey and mass screening and treatment activities as part of the Malaria Elimination Demonstration Project (MEDP) from 2019 to 2020. Isolated DNA samples were used to amplify the Pfdhfr, Pfdhps, Pfk13 and Pfmdr1 genes using nested PCR and sequenced for mutation analysis using the Sanger sequencing method. Results A total of 393 samples were subjected to PCR amplification, sequencing and sequence analysis; 199, 215, 235, and 141 samples were successfully sequenced for Pfdhfr, Pfdhps, Pfk13, Pfmdr1, respectively. Analysis revealed that the 53.3% double mutation (C59R, S108N) in Pfdhfr, 89.3% single mutation (G437A) in Pfdhps, 13.5% single mutants (N86Y), and 51.1% synonymous mutations in Pfmdr1 in the study area. Five different non-synonymous and two synonymous point mutations found in Pfk13, which were not associated to artemisinin resistance. Conclusion The study has found that mutations linked to SP resistance are increasing in frequency, which may reduce the effectiveness of this drug as a future partner in artemisinin-based combinations. No evidence of mutations linked to artemisinin resistance in Pfk13 was found, suggesting that parasites are sensitive to artemisinin derivatives in the study area. These findings are a baseline for routine molecular surveillance to proactively identify the emergence and spread of artemisinin-resistant parasites.